DECISION MAKING FOR PROJECT SELECTION IN PT. JKT WITH ANALYTIC HIERARCHY PROCESS (AHP) METHOD - R. Daffa Andaru Fawwaz Naufal; Pri Hermawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The focus of this study is how PT. Jawara Kanistha Tibra (JKT) makes decisions about three projects: "Reggae Festival", "A Night at the Orchestra: Dewa 19," and "Suara Akal Summit". PT. JKT faces challenges in choosing between three projects. Each project has different risks and benefits, and many different stakeholders participate in it. The Analytical Hierarchy Process (AHP) method is used to provide a systematic framework for evaluating and selecting the project that best aligns with the organization's strategic objectives. The results show that "A Night at the Orchestra: Dewa 19" received the highest score, indicating that this project meets all assessment criteria. This decision helps the company achieve its long-term goals in addition to short-term financial benefits. PT JKT can provide better direction for future project evaluation and selection by using a more objective and methodical approach.